TYPES OF SEMANTIC RELATIONS IN LEXICOGRAPHY - Roza Bahodirova; Madina Baratova (TADQIQOTLAR, 2026)
Abstract Lexicography is an important branch of linguistics that studies the theory and practice of dictionary making. One of the central aspects of lexicography is semantic relations, which explain how words are connected in meaning. Semantic relations help lexicographers organize vocabulary, define meanings accurately, and improve the quality of dictionaries. This article discusses the main types of semantic relations used in lexicography, including synonymy, antonymy, hyponymy, meronymy, polysemy, homonymy, and collocation. The study also explains the importance of semantic relations in language learning, communication, and modern dictionary compilation. Semantic analysis provides valuable support for both traditional and digital lexicography because it allows dictionaries to present lexical information in a more systematic and understandable way.